Morphological changes throughout the ontogeny of the pupal stage of Melanomoma viatrix (Diptera: Richardiidae) - VILLALOBOS-MORENO, ALFONSO; AGUDELO-M., JUAN CARLOS; BARAJAS-S., ANDRÉS FERNANDO; HERRERA-Q., SANDRA; CÉSPEDES, JUAN CARLOS (Revista Colombiana de Entomología, 2009)
The pupal stage of some Diptera occurs within a coarctate pupa formed by a thick and dark chorion which does not allow observing the events that occur in the interior and the dissection process is indispensable. The present study is based on observations of morphological changes that pineapple flies Melanoloma viatrix undergoes throughout its pupal stage. Pineapples infested with M. viatrix were collected in the locality of Palonegro (Lebrija, Santander, Colombia) and were dissected to extract larvae and to place them within 20 Petri dishes with sterilized sand, adding 14 larvae in each dish at ambient temperature (25ºC, 80% HR). Through 17 days, two pupae were taken for dissection and description of morphological changes. Between the first and the third day, lysis of tissues and tagmatization were observed. On the fourth day, the legs in formation were observed and on the fifth day the primordial wings and the structures which will become the eyes, were visible. On the seventh day, the mouth parts were evident. From the eighth to the tenth day no major morphological changes were observed. On the eleventh day, antennae and halters appeared. Finally, body coloration of the adult was registered on the thirteenth day.